Normal incidence of sound transmission loss of a double-leaf partition inserted with a micro-perforated panel - Putra, Azma; Ismail, Ahmad Yusuf; ramlan, roszaidi; Ayob, Md Razali; Sajidin, Muhammad (Hindawi, 2013)
A double-leaf partition in engineering structures has been widely applied for its advantages i.e. in terms of its mechanical strength as well as its lightweight property. In noise control, the double-leaf also serves to be an effective noise barrier. Unfortunately at low frequency, the sound transmission loss reduces significantly due to the coupling between the panels and the air between them. This paper studies the effect of a micro-perforated panel (MPP) inserted inside a double-leaf partition on the sound transmission loss performance of the system. The MPP insertion is proposed to provide a hygienic double-leaf noise insulator replacing the classical abrasive porous materials between the panels. It is found that the transmission loss improves at the troublesome mass-air-mass resonant frequency if the MPP is located closer to the solid panel. The mathematical model is derived for normal incidence of acoustic loading.